PERILAKU OPORTUNISTIK MANAJERIAL TERHADAP FREE CASH FLOW DAN NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DIBURSA EFEK INDONESIA - Misrah Misrah (Jurnal Ekonomi dan Bisnis Kontemporer, 2017)
This study aims to develop and analyze the effect of managerial opotunistic behavior on free cash flow and firm value on manufacturing companies listed on the Indonesian stock exchange. The result of the research showed that the variable of firm size (X1) to Free Cash Flow (Y1), obtained structural coefficient of -0.033, and P-value 0.336. Because P-value 0.05, Corporate Size (X1) to Corporate Value (Y2), structural coefficient is 0102, and P-value 0.002. Because P-value 0.05, Leverage (X2) to free cash flow (Y1), obtained structural coefficient of 0.037, and P-value 0.041. Because P-value 0.05, Leverage (X2) to firm value (Y1), obtained structural coefficient of -0.014, and P-value 0.681. Because P-value 0.05, Systemic Risk (X3) to free cash flow (Y1), obtained structural coefficient of -0.006, and P-value 0.861. Because P-value 0.05, Systemic Risk (X3) to firm value (Y2), obtained structural coefficient of 0.884, and P-value 0.000.